2015
DOI: 10.21608/ejrci.2015.9302
|View full text |Cite
|
Sign up to set email alerts
|

Study of The Role of Nicotinamide Phosphoribosyl Transferase/Visfatin in Patients with Systemic Lupus Erythematosus and Lupus Nephritis

Abstract: Introduction: Lupus nephritis (LN) is common and carries a high burden of morbidity in SLE patients. The adipokine ''visfatin'' is highly expressed in visceral fat, exerts several pro inflammatory functions and was demonstrated as a marker of endothelial dysfunction (ED) in chronic kidney disease (CKD). Aim of the work: To evaluate the state of serum visfatin in SLE patients and to detect its possible correlation to disease activity and kidney affection. Also, to define a possible correlation between the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Previously, acetylation was one of the epigenetic factors contributing to SLE [ 37 , 38 ]. Moreover, previous studies reported that altered transferases activity as glutathione S, gamma glutamyl, and nicotinamide phosphoribosyl transferases were associated with SLE [ 39–41 ]. In BPs enrichment, the target genes of circ-CDC27 were mainly enriched by the transcription regulation, Ubl conjugation, and neurogenesis pathways, while, circ-Med14 target genes were mainly involved in neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, acetylation was one of the epigenetic factors contributing to SLE [ 37 , 38 ]. Moreover, previous studies reported that altered transferases activity as glutathione S, gamma glutamyl, and nicotinamide phosphoribosyl transferases were associated with SLE [ 39–41 ]. In BPs enrichment, the target genes of circ-CDC27 were mainly enriched by the transcription regulation, Ubl conjugation, and neurogenesis pathways, while, circ-Med14 target genes were mainly involved in neurogenesis.…”
Section: Discussionmentioning
confidence: 99%